Il campo di battaglia di ragione e sentimento. Husserl sulla storia della filosofia alla ricerca di un’etica fenomenologica - Römer, Inga (Bollettino Filosofico, 2024)
Husserl’s search for a phenomenological ethics, initially conceived of as a practical science analogous to an a priori theoretical science, was shaped by several historical sources. The article shows which sources influenced Husserl in what way. A first part discusses Brentano’s and Jodl’s influence on how Husserl approaches ethics. Part two to five follow Husserl’s interpretations and critique of the history of ethics from Socrates to Fichte. A final part discusses the history of ethics viewed from the standpoint of Husserl’s late ethics. The article culminates in the question as to whether Husserl’s conception of ethics stood in a certain tension to what he actually discovered in his phenomenological analyses of ethical phenomena. Keywords: Brentano, Feeling, Fichte, Jodl, Husserl, Reason, Shaftesbury